Electronic contract - Baadeche, Saad (Journal of Human Sciences, 2021)
The States have realised the importence of software  and  informatics in contemporary life as a matter of economic importence this  development  has resulted in a new pattern of transactions as well astrade exchanges  through an electronic medium  and in a virtual world  that does not recognize the geographical boundaries and  has been referred to as. Commerce which has become a reality in every aspect of the world The giant companies such as amazon and alibaba are the only ones to do so  this may be asked by many intellectuals businessmen and legislators and discussions are still on going and studies are far- reaching at the Level of bodies and organizations regional and global levels and considering algeria.as a  Part of this fast and evolving world  many laws have beene enacted  which regulates the work of the electronic contract though it is going slowly to catch up developed countries in this field .